How do sea urchins prepare offspring to face ocean acidification? Gamete intraspecific differences and adaptability - Asnicar, Davide; Locatello, Lisa; Zanovello, Laura; Minichino, Riccardo; Masiero, Luciano; Munari, Marco; Marin, Maria Gabriella (Frontiers in Marine Science, 2024)
Introduction Due to their relevant ecological position and well-studied biology, sea urchins are reference organisms for ocean acidification studies, at both within- and trans-generational levels. In this study, we examined gamete quality in specimens exposed to future predicted (-0.4 units) pH conditions during gametogenesis. Methods Egg physical characteristics, biochemical composition, and fatty acid profiles were assessed after two and six months of exposure, while sperm viability and velocity were analyzed after six months of exposure. Considering the documented intraspecific variability in response to ocean acidification, this study involved two populations of Paracentrotus lividus. One population was sampled from the highly variable lagoon of Venice (Site 1), while the other was obtained from a coastal area (Site 2) characterized by more stable environmental conditions and facing minimal anthropogenic stress. Results A different response was highlighted in the two sites. Noteworthy trends emerged, especially in the fatty acid profile and sperm traits. Although adults were fed the same diet, Site 1 eggs contained more high-energetic fatty acids than Site 2, potentially boosting the survival odds for the next generation. Moreover, Site 1 sperms displayed higher viability but slower motility compared to those from Site 2. Within sites, a significant difference between time points and a change in the fitness strategy of sea urchin females emerged when comparing eggs spawned after two and six months of exposure to reduced pH. The effects of time and exposure pH are more pronounced in animals from Site 1, suggesting a higher adaptability of this population rather than negative effects of ocean acidification. Discussion Overall, our findings suggest that sea urchins have the potential to acclimate to reduced pH and to produce gametes of the same quality as controls held at the currently natural pH. Our findings emphasize the relevance of combining investigations of gamete quality characteristics, particularly egg biochemistry and fatty acid composition, and considering site variability to fully understand the transgenerational response potential of sea urchins to ocean acidification.